Determining and comparing the activity requirements and participation experiences of Xhosa Women with stroke in relation to life roles in rural and urban environments - Enright, Marlie (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScPhysio)--Stellenbosch University, 2017.